Teaching English Vocabulary Using Comic Strips - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2018)
This research aims to describe the use of comic strip in teaching English vocabulary to seventh graders of SMPN 3 Poso. This research is qualitative in nature, where the data are collected through observation. The findings show that the teaching and learning process was conducted in two meetings and test was administered after the meetings, and all students show satisfied achievement when comic strip is used in teaching and learning activities (27% are excellent, 63,6% students are good, and 9,0% students are good).Keywords: vocabulary acquisition, comic strips